Spectrophotometric determination of ceftazidime in pharmaceutical preparations using neocuproin as a complexing agent - Moreno, Andreia de Haro [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis Inc, 2008)
A simple and reproducible spectrophotometric method for the assay of ceftazidime with neocuproin-copper(II) reagent has been developed. The procedure is based on the drug in an acidic medium, subsequent formation of yellow ternary complex in citrate buffer solution (pH 4.2), and measurement at 454 nm. Beer's law is obeyed in the range 15.0-40.0 mu g mL(-1) with correlation coefficient r(2) = 0.9995. The procedure holds good accuracy and precision when applied to the analysis of ceftazidime in powder for injection with good recovery percent ranging from 100.17 +/- 1.0 without interference from additives.
Keywords: ceftazidime; pharmaceutical analysis; quality control; spectrophotometry